Pengaruh Kepemimpinan Terhadap Disiplin Kerja, Motivasi Kerja Dan Kinerja Perawat Pelaksana Di Ruang Rawat Inap RSJ Menur Surabaya - Brahmasari, Ida Aju (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2014)
Nurse performance define by nurse activity in implementation of authority, duty and its responsibility in order to fundamental duty target attainment of profession and existing of certifiable treatment upbringing. This research is to prove and analyse the leadership influence to work discipline, leadership to work motivation, work discipline to performance, work motivation to performance and leadership influence to performance of nurse who take care of patients at ward of the RSJ Menur Surabaya. This research is performed in ward of the RSJ Menur Surabaya with the responder of nurse as much 76 people. Research instrument by kuesioner and use the Likert scale to collect the data, while analysis constructively program the Smart PLS 2.0. Result of analysis find the existence of significancy relation between leadership and discipline (t statistic: 5,192), leadership and motivation (t statistic: 2,294), and between motivation and performance (t statistic: 4,251). While relation do not signifikan between discipline and performance (t statistic: 1,362) and between leadership and performance (t statistic: 0,209). This research founded that Leadership have influence which are positive and significan to work discipline, Leadership have influence which are positive and signifikan to work motivation, Work Discipline have influence which are positive but do not signifikan to performance, Work Motivation have influence which are positive and signifikan to performance and Leadership have influence which do not signifikan to performance of nurse who take care of patients at ward of the RSJ Menur Surabaya. Among work discipline variable, work motivation, leadership, and performance, founded that leadership have the biggest influence at work discipline, and performance very influenced by work motivation of nurse who take care of patients at ward of the RSJ Menur Surabaya. Key word: leadership, work discipline, work motivation, nurse performance.